Entrapment of guidewire in left anterior descending artery: Surgical management. (July 2017) - Idhrees, A Mohammed; Radhakrishnan, Bineesh K; Panicker, Vargheese T; Pillai, Vivek; Karunakaran, Jayakumar
Entrapment of a guidewire during coronary artery interventions is rare and requires prompt treatment. A 52-year-old man underwent a primary percutaneous transluminal coronary angioplasty to the left anterior descending artery. A fractured guidewire was retained in the distal left anterior descending artery, which caused left ventricular dysfunction and total occlusion of the left anterior descending artery. He underwent endarterectomy with removal of the guidewire and bypass grafting. He had a normal postoperative period. The modalities for management of an entrapped guidewire are discussed.